Heterogeneity, Displacement, and Alienation in Desai’s The Inheritance of Loss - Shrivastwa, Bimal Kishore (NUTA Journal, 2021)
The paper aims to explore the postmodern issues such as heterogeneity, displacement, and alienation in Kiran Desai’s novel, The Inheritance of Loss with respect to its impact on the Indian lifestyle and culture. To analyze how this fiction demonstrates the impact of globalization, racial contempt, and alienation, illegal immigration, diasporic communities, hybridization, and cultural infiltration with special reference to the characters, such as Biju, who grow up within the novel, the research tool taken for the research is postmodern theoretical perspectives advocated by Jean-Francois Lyotard, Michel Foucault, and Jean Baudrillard. Applying the qualitative research method, and collecting data through the close reading of the text, The Inheritance of Loss from the context of postmodernity, the paper seeks to display how Desai limns the problems of insurgency, declining moral standard, and behavior of individuals, increasing corruption in the Indian society after its independence. The chief finding of the research is that characters like Sai and Gyan lose love, Biju loses his possessions, Lola and Noni lose their dignity and privacy of their house, Jemubhai loses his Indianness. It is expected that scholars interested to study postmodernity in Desai can take the paper as a reference.